Thermodynamic Evaluation of Equilibrium Oxygen Composition of UO2-Mo Nuclear Fuel Pellet Under High Temperature Steam - Yang, Jae Ho; Song, Kun Woo; Kim, Dong Seok; Kim, Dong-Joo; Lee, Heung Soo; Yoon, Ji-Hae; Koo, Yang-Hyun (Frontiers in Energy Research, 2021)
Micro-plate or microcell UO2–Mo is considered a promising accident tolerant fuel candidate for water-cooled power reactors. In this work, we evaluated the anticipated oxidation behavior of a UO2–Mo system under high-temperature steam to understand the impact of Mo oxidation on the fuel degradation mechanism in the event of steam ingress through cracks in the cladding. The equilibrium oxygen compositions of UO2 and Mo in various steam atmospheres relevant to reactor operating conditions were predicted using thermodynamic calculations and then compared with previous results. The oxidation behavior of UO2–Mo pellets was discussed through thermodynamic calculations and in terms of kinetic parameters such as oxygen diffusion, fuel temperature profile, and pellet microstructure. Mo oxidation was found to have an insignificant effect on pellet integrity in a cladding leakage scenario under normal reactor operating conditions.